School ARventure: A design thinking framework for gamified augmented reality mathematics learning for students with intellectual disabilities - Erika Kurniasari; Ida Dwijayanti; Nizaruddin (CV. FOUNDAE, 2026)
Background: Students with intellectual disabilities often experience difficulties in learning mathematics due to limitations in working memory, challenges in processing abstract symbols, and the limited availability of adaptive learning media in special education settings. In many special schools, mathematics instruction still relies on static physical manipulatives that provide limited opportunities to connect abstract mathematical ideas with meaningful learning experiences. Aims: This study aims to propose a conceptual design framework called School ARventure, a gamified Augmented Reality mathematics learning environment integrated with a three-dimensional school model to support contextual mathematics learning for students with intellectual disabilities. Method: This research employed a qualitative design guided by the Design Thinking framework, focusing on the stages of Empathize, Define, and Ideate. Data were collected through classroom observations, questionnaires, and semi structured interviews involving teachers and students from three special education schools. The instruments were validated by experts, and the data were analyzed using thematic analysis to identify learning barriers, user needs, and design requirements. Results: The study produced an initial design framework addressing three main needs: concrete visualization of numerical quantities, reduced motor demands in measurement activities, and simplified representation of mathematical word problems. Three AR based features were conceptualized: AR Counting Adventure, AR Length Virtual Ruler, and Animated Story Quest, integrated with a physical school model as a contextual anchor. Conclusion: The findings present School ARventure as a Design Thinking based framework for gamified Augmented Reality mathematics learning for students with intellectual disabilities and provide a foundation for future prototype development and empirical evaluation.